HUBUNGAN LINGKUNGAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI DI KANTOR CAMAT AMANDRAYA KABUPATEN NIAS SELATAN - Iwanti Halawa (Universitas Nias Raya, 2023)
The purpose of this study was to determine the relationship between the work environment and the effectiveness of employee work at the Amandraya Sub-district Office, South Nias Regency. The type of research used is a quantitative type of causal nature. The source of the data was employees, with the population and sample in this study being 33 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple correlation analysis. The results of this study showed that the correlation value was 0.696. This research can be concluded that there is a strong relationship between the work environment and the effectiveness of employee work at the Amandraya Sub-district Office, South Nias Regency. The suggestions for this study are (1) In improving the effectiveness of employee work, the work environment should be cleaned and neatly arranged to facilitate work implementation activities. (2) To increase comfort in carrying out work, it is better for each workspace to be given facilities such as air conditioning.